UPAYA MENINGKATKAN KINERJA PEMASARAN PADA UMK DURIAN JATUHAN DI DAERAH BANTEN - Reni Febriani; Achmad Irfan Firdaus (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
This study aims to determine the effect of market orientation and environmental adaptability through product innovation on marketing performance. The samples studied were durian MSME actors (in the form of durian or durian processed) that were registered with the Banten Durian Entrepreneur Group (KPDB) with 70 businessmen in the Serang, Cilegon, Pandeglang and Lebak regions. Sources of research data are obtained from online questionnaires using google forms tools that are distributed via the whatsapp media group. Data processing uses the Structural Equation Model (SEM) approach with Smart PLS 3.0 Software. The results showed that market orientation and environmental adaptability didn’t have a positive effect on marketing performance, environmental adaptability didn’t have a positive effect on product innovation, market orientation have a positive effect on product innovation, and product innovation have a positive effect on marketing performance. From the results of this study indicate that MSEs have not been consistent in improving marketing performance, because durian is still classified as seasonal fruit and the price is high when it is out of season.